Novel approaches in the high-risk prostate cancer patient: Summary of key research presented at AUA 2014 - Editorial, CUAJ (Canadian Urological Association Journal, 2014)
Another topic of focus at AUA 2014 was subgroup of prostate cancer patients deemed to be at high risk.